Kerley a line in an 18-year-old female with acute pulmonary edema and chronic kidney disease stage V - Salim Winarno, Agus Nur (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
The incidence of chronic kidney disease (CKD) continues rising recently. Chronic kidney disease is associated with many multiple complications. One of the complications related to the emergency situation is acute pulmonary edema (APE). Acute pulmonary edema is a condition where there is acute fluid accumulation in the lungs. Acute pulmonary edema can cause respiratory distress and severe hypoxia. Early recognition and initial treatment shall be considered to prevent further morbidity and mortality. This will be presented a case of 18-year-old female who came to the hospital with progressive dyspnea. After further diagnostic procedures, diagnosis of APE and CKD are constructed. Initial treatment in the emergency room did not give a good response. Then, the patient referred to the higher level hospital to receive possible dialysis treatment.